2017
DOI: 10.1108/ijif-07-2017-002
|View full text |Cite
|
Sign up to set email alerts
|

Application of waqf for social and development finance

Abstract: Purpose -This paper aims to discuss the application of waqf (endowment) in the social finance sector for funding social and development projects and services.Design/methodology/approach -The study is qualitative. It reviews literature and provides descriptive data to present its main idea.Findings -Most Muslim-majority countries are generally income-poor, and the governments are generally weak in their tax collection, effective governance and capacity for development spending. Private sector financial institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 21 publications
1
76
0
17
Order By: Relevance
“…In other words, IFI employees would be more ready to accept the SFIs when they have a greater awareness of the instruments. This is in line with Shaikh et al (2017) who suggested that it is important to create social awareness before creating the right kind of alternative instruments at the right place. The awareness about the progress made and actions needed to end poverty would develop people's thinking about their lives and raise expectations about what is possible in the future (World Bank, 2017).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In other words, IFI employees would be more ready to accept the SFIs when they have a greater awareness of the instruments. This is in line with Shaikh et al (2017) who suggested that it is important to create social awareness before creating the right kind of alternative instruments at the right place. The awareness about the progress made and actions needed to end poverty would develop people's thinking about their lives and raise expectations about what is possible in the future (World Bank, 2017).…”
Section: Resultssupporting
confidence: 84%
“…According to Haneef, Pramanik, Mohammed, Dahiru, and Amin (2013), 31 per cent of the total population of these countries live in poverty and in the 57 member countries of the Organisation of Islamic Cooperation (OIC), many people live on average incomes below US$1.25 per day. Shaikh, Ismail, and Shafiai (2017) point out that there is an enormous need for the development of infrastructure and spending in the largely income-poor Muslim world since the size and the scope of the formal-sector of financial institutions in these countries are small and concentrated.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to direct cash waqf model, this model has been widely practiced in the One important aspect of waqf fund management is the long-term strategy that accommodates both current and future charitable goals. Solely relying on donation decreases the likelihood of financial sustainability in the long-run (Shaikh et al, 2017) because it largely depends on the generosity of the human behaviours. Just like profitoriented organisations, diversifying sources of income is important for non-profit organisations like waqf institutions, whereby financial risks could be minimised by holding a diversified portfolio of assets with varying levels of liquidity risk (Ambrose et al, 2018).…”
Section: Indirect Cash Waqf Modelmentioning
confidence: 99%
“…An Islamic worldview is rooted in two inseparable aspects: duniya (temporal worldly life) and the akhirah (afterlife). Muslims are encouraged to behave well and strive for excellence to obtain satisfaction in eternal life (Abdul Aziz et al, 2019;Mohsin et al, 2016;Shaikh et al, 2017). The Islamic ideology of a two-world framework of life leads to participation in social causes and selfless behaviour in charitable giving (Shaikh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The ideology paradigm focuses on everything that culminates in the belief in God's Perseverance must be accompanied by the awareness of the realization of social justice. Meanwhile, in the context of the socio-economic paradigm, waqf alternatively contributes to problemsolver in economic issues occurred in society (Shaikh et al, 2017). In other word, waqf provides a solution for economic inequality problems in society (Amuda, 2013;Shaikh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%